2007
DOI: 10.1379/csc-275.1
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated synthesis of p8, a stress-associated transcription cofactor, in diapause-destined embryos of Artemia franciscana

Abstract: Diapause-destined embryos of the crustacean Artemia franciscana arrest as gastrulae, acquire extreme stress tolerance, and enter profound metabolic dormancy. Among genes upregulated at 2 days postfertilization in these embryos is a homologue of p8, a stress-inducible transcription cofactor. Artemia p8 is smaller than vertebrate homologues but shares a basic helix-loop-helix domain and a bipartite nuclear localization signal. Probing of restriction digested DNA on Southern blots indicated a single Artemia p8 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 56 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…This is a nuclear DNA-binding protein, which is strongly activated in response to several stresses, and, on the basis of functional similarity to HMG-I/Y-like proteins, it has been suggested that p8 may be involved in transcription regulation (Encinar et al, 2001; Hoffmeister et al, 2002). It plays an important role in such a basic biological process as ontogeny and hence is involved in a variety of developmental processes, such as pancreatic development in rats (Mallo et al, 1997), temporal expression of the beta subunit of luteinizing hormone (LHB) during gonadotroph development in mice (Million Passe et al, 2008), and mediation of gene expression in the diapause-destined crustacean Artemia franciscana (Qiu and MacRae, 2007). …”
Section: Macrolidesmentioning
confidence: 99%
“…This is a nuclear DNA-binding protein, which is strongly activated in response to several stresses, and, on the basis of functional similarity to HMG-I/Y-like proteins, it has been suggested that p8 may be involved in transcription regulation (Encinar et al, 2001; Hoffmeister et al, 2002). It plays an important role in such a basic biological process as ontogeny and hence is involved in a variety of developmental processes, such as pancreatic development in rats (Mallo et al, 1997), temporal expression of the beta subunit of luteinizing hormone (LHB) during gonadotroph development in mice (Million Passe et al, 2008), and mediation of gene expression in the diapause-destined crustacean Artemia franciscana (Qiu and MacRae, 2007). …”
Section: Macrolidesmentioning
confidence: 99%
“…In Artemia , various genes associated with response to environmental changes have been identified, such as BRCA1 , p8 , artemin , ArHsp21 , ArHsp22 , and p26 ( Qiu et al, 2007 ; Qiu and MacRae, 2008a , Qiu and MacRae, 2008b ; Liu et al, 2009 ; Dai et al, 2011 ; King et al, 2013 ; King et al, 2014 ; Zhou et al, 2014 ; Ye et al, 2017 ). Specifically, these genes have been related to the diapause reproductive mode, such as BRCA1 and p8 ( Qiu et al, 2007 ; Qiu and MacRae, 2007 ), and also with cyst resistance to stress, such as artemin ( King et al, 2014 ), SGEG ( Liu et al, 2009 ), Arp-CBP ( Wen-Ming et al, 2013 ), and SGEG 1 and SGEG 2 ( Dai et al, 2011 ). In the latter two cases, their function would be related to the formation of the chorion outer layer, which protects the encysted embryo from adverse environments ( Dai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes two peptides ( SGEG 1 and SGEG 2) secreted by the shell gland, which conform to the outer and inner layers of the chorion ( Dai et al, 2011 ). In the case of the genes related to cellular division, Qiu and MacRae (2007) described p8 gene, which presents increased expression one day postfertilization in diapause-destined embryos. This class of genes has also been associated with diapause in A. franciscana and is often upregulated, in this species ( BRCA1 and p8 ) ( Qiu et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the knockdown of the stress-induced transcription factor p8 by RNAi causes approximately 50% of A. franciscana cysts to hatch prematurely by 36 h after release from females (King, 2013). p8 is developmentally regulated in Artemia embryos and progressively accumulates in the nuclei of encysted embryos (Qiu and MacRae, 2007;Lin et al, 2016). ArHsp40 may assist in the translocation of p8 or other transcription factors into nuclei, thereby promoting transcription of genes that arrest the cell cycle and depress metabolism, as occurs during diapause.…”
Section: Discussionmentioning
confidence: 99%